TITRATION METHOD OF AB0 ANTIBODIES WITH THE USE OF MODERN GEL TECHNOLOGY IN AB0-INCOMPATIBLE TRANSPLANTATION - A. K. Porunova; V. V. Morozova; I. E. Tsiroulnikova; O. M. Tsiroulnikova; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2014)
It is shown that developed method of titrating AB0 antibodies allows defi ning the titer of the investigational antibodies more precisely on 1–3 dilution of serum compared to the prototype method (titration method of antibodiesin saline medium on the plane). It is more obvious as it excludes hardly interpretable results due to the possibility of conducting visual assessment of agglutination reaction in the gel card thick column and requires less time foranalysis. The results can be saved for comparison with the results of further research. That is not possible under prototype titration method. Aim: our aim is to create a laboratory technique that can accurately, reliably and clearly produce titration of AB0 system antibodies, including in patients with low initial concentration of agglutinins in the blood; a technique more economical in terms of spending serum and that takes less time.Materials and methods: those modes were empirically chosen which allow titration of AB0 system agglutinins using gel technology based micro typing; to titer group antibodies 1640 serum assays of recipients in AB0-incompatibletransplantation were analyzed.The result of the use of specially developed method in organ transplantation from incompatible blood donors consists in enhancing accuracy, sensitivity of natural, complete and incomplete AB0 system immune antibodies titration, in its clarity, using of blood micro-doses for earlier detection of sensitizing of the patient, which is especially important in Pediatrics. Conclusion: the developed procedure of AB0-antibodies’ titration using modern gel technology makes possible a more precise monitoring of the titer of antibodies that is necessary to predict the graft rejection risk, to select the Protocol of preoperative preparation and postoperative management of patients, to assess the effectiveness of therapy in patients for whom it is diffi cult to fi nd a compatible blood type donor, and for whom today AB0-incompatible transplantation is a life-saving.